Power, Knowledge, and Language Hegemony from the Perspective of Michel Foucault - Rahmatullah; Arlin Adam; Syamsu A. Kamaruddin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
Philosophy is present to answer human questions that are not addressed by other fields of knowledge. Every branch of knowledge begins with philosophy and ends with art. This means that all sciences, both natural and social sciences, originate from philosophy before undergoing further development. As the foundation of knowledge, philosophy questions sciences based on ontological, epistemological, and axiological aspects. This paper is compiled from a literature review (library research method) of Foucault's works, the works of theorists mapping Foucault's social thoughts, and research based on Foucault's approach. The literature study method is a study used to gather information and data with the help of various materials available in the library, such as documents, books, magazines, and so on. Many contributions have been made by Foucault to the intellectual world, whether in philosophy, culture, social, political, or artistic fields. One of Foucault's significant contributions in philosophy and politics is his concept of power. Therefore, acquiring knowledge through educational programs requires power, in this case, referring to proficient language abilities, and conversely, gaining power requires knowledge. Knowledge indeed holds power and brings about authority, and obtaining knowledge also requires authority. The results of this thinking can be observed in real-life, such as in the United States, which has become a superpower due to the abundance of information received and language hegemony that demonstrates a balance of power.